AKTUALISASI IDENTITAS KAUM WARIA DALAM PERTUNJUKAN LUDRUK - Agus Sukamto (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
The object of this research is identity actualization of intersex in Ludruk Irama Budaya Surabaya show. Ludruk is one of art traditional show in east java. Ludruk and the life of all the members is a phenomenon for Surabayanese people One of the members is intersex. They are considered to be able to give any entertainment on the stage in ludruk show. Their ability to create any dancing movement and make any improvisation on the stage shows that they have their own way to actualize their identity. The strategy is done by showing the beauty in their bodies. Any ways like showing up their big breasts, wearing wigs,showing up their erotic body movements, and any accessories. For the intersex members, all of those things are the way for them to find satisfaction because the life outside the ludruk show is just as their side life. In the ludruk esthetic shows, the intersex members in any ways want to be claimed as beautiful women. It means that intersex people use ludruk shows as one of the ways to show their real identity to audience. Identity perspective through its approach will deal with all process of intersex people to get their self identity on the stage but also in social life. The life of intersex on the stage is considered to be important because for them on the stage they can show their femininity. Having tender movement does not mean to imitate any movement of dances in Javanese palaces, attitude and behaviour. It’s about how they reflect women’s attitude and behaviourand imagine to be themselves. The identity actualization of intersex will not happen without response and reaction from audience. For audience, the intersex activities on the stage is an entertainment. Audience will give any comments at the time the intersex people do any funny activities that can cause them laugh and arise their passion. The intersex movements will be considered as better movements compared with any real womwn’s movement. The intersex are still considered to be an entertaining show, not as people with admited existence. Therefore, in estetic world the intersex fight for their rights as human beings.Keywords: identity,esthetic, actualization